FRI0185 HYDROXYCHLOROQUINE FOR THE PREVENTION OF RELAPSES IN A SERIES OF 812 PATIENTS WITH PRIMARY ANTIPHOSPHOLIPID SYNDROME: THE HIBISCUS RETROSPECTIVE STUDY. (June 2019) - Belizna, Cristina; Stojanovich, Ljudmila; Saulnier, Patrick; Pregnolato, Francesca; Alijotas-Reig, Jaume; Esteve-Valverde, Enrique; Latino, Omar; Udry, Sebastien; Stanisavljevic, Natasa; Makatsariya, Alexander; Khizroeva, Jamilya; Limper, Maarten; et al.
Abstract : Background: The relapse rate in antiphospholipid syndrome (APS) remains high, 20% at 5 years in thrombotic APS and 28% in obstetrical APS (1). Hydroxychloroquine (HCQ) appears as an additional therapy, with immunomodulatory and antithrombotic effects (2-5). Objectives: The main aim of this trial is to assess the efficacy of treatment with Hydroxychloroquine in preventing new events in primary antiphospholipid syndrome patients. Methods: We have performed a retrospective multicentre open-labelled study (2002-2018). Results: 812 patients with APS from 53 international centres from 16 countries were included. In all cases, the previous standard treatment was inefficient. The mean follow-up was 20.2 months (8- 144 mo), the mean age 39.5 years old. The type of clinical manifestations is described in figure 1 . The obstetrical manifestations were various as described in figure 2 . The number of thrombotic events were 190 arterial and 187 venous. Triple antiphospholipid antibody (tAPL) positivity was found in 20% of patients and lupus anticoagulant (LA) in 22%. No bleeding was registered in 99, 6% of cases with treatment by HCQ. HCQ use was associated with favourable outcome in 96% of cases (figure 3 ). In multivariate analysis, age more than 65 years was associated with arterial events (odds-ratio 0.13 95%CI 0.03-0.32, p 0.005). Conclusion: HCQ could be effective in cases of refractory APS but prospective studies are necessary. References: [1] Cervera R, Serrano R, Pons-Estel GJ, Ceberio-Hualde L, Shoenfeld Y, de Ramón E, Buonaiuto V, Jacobsen S, Zeher MM, Tarr T, Tincani A, Taglietti M, Theodossiades G, Nomikou E, Galeazzi M, Bellisai F, Meroni PL, Derksen RH, de Groot PG, Baleva M, Mosca M, Bombardieri S, Houssiau F, Gris JC, Quéré I, Hachulla E, Vasconcelos C, Fernández-Nebro A, Haro M, Amoura Z, Miyara M, Tektonidou M, Espinosa G, Bertolaccini ML, Khamashta MA. Morbidity and mortality in the antiphospholipid syndrome during a 10-year period: a multicentre prospective study of 1000 patients. Ann Rheum Dis. 2015;74:1011-8. [2] Belizna C. Hydroxychloroquine as an anti-thrombotic in antiphospholipid syndrome. Autoimmun Rev. 2015;14:358–62. [3] Nuri E, Taraborelli M, Andreoli L, Tonello M, Gerosa M, Calligaro A, Argolini LM, Kumar R, Pengo V, Meroni PL, Ruffatti A, Tincani A. Long-term use of hydroxychloroquine reduces antiphospholipid antibodies levels in patients with primary antiphospholipid syndrome. Immunol Res. 2017;65:17-24. [4] Schmidt-Tanguy A, Voswinkel J, Henrion D, Subra JF, Loufrani L, Rohmer V, et al. Antithrombotic effects of hydroxychloroquine in primary antiphospholipid syndrome patients. J Thromb Haemost JTH. 2013;11:1927–9. Disclosure of Interests: Cristina Belizna: None declared, Ljudmila Stojanovich: None declared, Patrick Saulnier: None declared, Francesca Pregnolato: None declared, Jaume Alijotas-Reig: None declared, Enrique Esteve-Valverde: None declared, Omar Latino: None declared, Sebastien Udry: None declared, Natasa Stanisavljevic: None declared, Alexander Makatsariya: None declared, Jamilya Khizroeva: None declared, Maarten Limper Consultant for: GSK, Roche and Thermofisher, Speakers bureau: GSK and Roche, Angela Tincani Consultant for: UCB, Pfizer, Abbvie, BMS, Sanofi, Roche, GSK, AlphaSigma, Lillly, Jannsen, Cellgene, Novartis, Laura Andreoli: None declared, Francesca Regola: None declared, Cecilia Chighizola Speakers bureau: Inova Diagnostics, Maria Orietta Borghi: None declared, Sule Apras Bilgen: None declared, Levent Kılıç: None declared, Arsene Mekinian: None declared, Valentina Canti: None declared, Katrien Devreese: None declared, Gilberto Pires Rosa: None declared, Laura Damian: None declared, Fatma Said: None declared, Yehuda Shoenfeld: None declared, Ricard Cervera: None declared, Pier Luigi Meroni Consultant for: Inova, Thermofisher, Teofarma, Zahir Amoura: None declared